Automatic Budget Stabilization in the EU During 2007-2017 - Ignatov, Ignat (Research Papers, 2020)
The capacity to flatten the economic cycle through the automatic stabilizers differs among the EU member states. The aim of this paper is to provide quantitative estimates of the different capabilities for automatic budget stabilization among the EU countries in 2007-2017. The paper provides evidence that the difference in the strength of the stabilizers among the EU countries could be attributed to certain features of their tax systems. Specifically, there have been outlined the dominant influence of the indirect taxes compared to that of the direct taxes in the budget structure, the type of the income taxation and the maximum marginal tax rate.
Keywords: Automatic stabilizers; Business cycle; Budget revenues; Fiscal discipline